The Effect of Cold Compress on Reducing Intravenous Pain in the First Active Phase - Rosalinna, Rosalinna (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
Pain in the delivery process is caused by uterine contractions which cause cervical dilatation and hypoxia in the uterine muscles. One effort to help reduce labor pain in the active phase 1 is by applying cold compresses . The cold compress will numb the affected area by slowing the transmission of pain through the sensory neurons . This study aims to determine the effect of cold compresses on reducing labor pain in the active phase 1 at Dr. Oen Solo Baru . : This type of research is quantitative research with a quasy experimental design . The research design uses pre and post test group design. The research sample was 30 mothers during the first active phase of labor in the maternity ward of Dr. Oen Solo Baru. The research instrument was a cold compress given for 20 minutes and a pain intensity measuring instrument according to Numerical Rating Scale ( NRS ). Data analysis used the Wilcoxon test . Most of the respondents before being given a cold compress experienced labor pain during the first active phase of the heavy category. All of the respondents after being given a cold compress experienced labor pain when I was in the moderate category of active faeces. The average level of labor pain during the first active phase before being given a cold compress for 20 minutes was 6.83. The average pain level during labor during the first active phase after being given cold compresses decreased to 5.33. The Wilcoxon test results obtained obtained p-value = 0.000 . There is an effect of cold compresses on reducing labor pain during the first active phase at Dr. Oen Solo Baru with p = 0.000 . There is an effect of cold compresses on reducing labor pain during the first active phase at Dr. Oen Solo Baru . Cold compresses can be an alternative in reducing labor pain.